2014
DOI: 10.1890/13-0025.1
|View full text |Cite
|
Sign up to set email alerts
|

Synergism and context dependency of interactions between arbuscular mycorrhizal fungi and rhizobia with a prairie legume

Abstract: Abstract. Biotic interactions play primary roles in major theories of the distribution and abundance of species, yet the nature of these biotic interactions can depend upon the larger ecological community. Leguminous plants, for example, commonly associate with both arbuscular mycorrhizal fungi (AMF) and rhizobia bacteria, and the pairwise interactions may depend upon the presence or identity of the third partner. To determine if the dynamics of plant-AMF and plant-rhizobia interactions are affected by the alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
120
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 44 publications
15
120
3
2
Order By: Relevance
“…We found that plants in tripartite interactions had a significantly higher root and shoot biomass, N tissue concentrations and contents, and P contents than plants that were only colonized by rhizobia or AM fungi (Figures a,b; c,d; and S3a,c). Synergistic responses in tripartite interactions have also been described by other authors especially under low P and N supply conditions (Bournaud et al, ; Larimer et al, ). The dual inoculation with rhizobia and AM fungi can lead to higher photosynthetic rates and improves the harvest index (proportion of seed yields in relation to the total plant biomass) of legumes (Afkhami & Stinchcombe, ; Kaschuk, Kuyper, Leffelaar, Hungria, & Giller, ).…”
Section: Discussionsupporting
confidence: 68%
“…We found that plants in tripartite interactions had a significantly higher root and shoot biomass, N tissue concentrations and contents, and P contents than plants that were only colonized by rhizobia or AM fungi (Figures a,b; c,d; and S3a,c). Synergistic responses in tripartite interactions have also been described by other authors especially under low P and N supply conditions (Bournaud et al, ; Larimer et al, ). The dual inoculation with rhizobia and AM fungi can lead to higher photosynthetic rates and improves the harvest index (proportion of seed yields in relation to the total plant biomass) of legumes (Afkhami & Stinchcombe, ; Kaschuk, Kuyper, Leffelaar, Hungria, & Giller, ).…”
Section: Discussionsupporting
confidence: 68%
“…Synergistic effects on plants of rhizobial and mycorrhizal symbioses have been described (e.g., Kaschuk et al, 2010; Larimer et al, 2014; van der Heijden et al, 2016), but the interaction of the two symbionts may also reduce plant growth (e.g., Bethlenfalvay et al, 1982; Ballhorn et al, 2016). As pointed out in a review by Larimer et al (2010), there is a need for more experimental studies relating the interaction of the symbionts to abiotic conditions because nutrient availability and other environmental factors may influence the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Ballhorn et al (2016) reported interactive effects of AM and rhizobial symbioses depending on light availability. Surprisingly, however, there is only limited and inconclusive information on how the interaction of the two symbionts changes along the P-availability gradients (see Bethlenfalvay et al, 1982; Larimer et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nearly all organisms are also 'infected' with diverse, commensal microbial communities [5][6][7][8]. As in free-living ecosystems [9,10], these diverse communities of co-occurring pathogenic and non-pathogenic species may interact directly and indirectly, both with each other and with their environment (the host). Interactions among these species can have major consequences for the presence of a species (the ability of a parasite to infect a host [11]), species abundance (parasite burden/levels of parasitaemia [12]), the invasibility of a host to a novel parasite (i.e., host susceptibility to secondary infection [13]), and host response to infection (e.g., clinical impact of infection or consequences for other coinfecting species [14]).…”
mentioning
confidence: 99%